KALIMAT PENOLAKAN DALAM BUKU TEKS SEJARAH INDONESIA KELAS XII SMA SWASTA MEGATAMA KOTA JAMBI - Monica Rustam; Abdoel Gafar; Firman Tara (Universitas Batanghari, 2021)
In the Indonesian History textbook, there are direct and indirect refusal sentences. It is said directly if the sentence conveyed can be understood as a refusal, such as a word no when it is uttered, then the sentence has described the refusal; if the sentence has an ambiguous or unclear meaning, then it is said as indirect refusal. This research aims to describe the sentence of refusal by using the word no or equivalent, reasons, conditions, suggestions or choices, and comments. The research was conducted by using a qualitative descriptive method. The data was collected by using the documentation technique. This research found five forms of refusal sentences include refusal by using the word no or equivalent, refusal by using reason, refusal by using terms, refusal by using proposals or choices, refusal by using comments. Thus, it can be concluded that an invitation, offer and request are not always fulfilled so that a refusal speech occurs, a refusal can be spoken based on the form so as not to be disappointed.